Direitos da natureza e desenvolvimento sustentável : desafios jurídicos, evolução constitucional e impactos sociais - Rohde, Stéphanie Taís (2025)
The research analyzes the relationship between the recognition of the rights of nature and sustainable development policies, examining their social and economic impacts on communities affected by environmental disasters, with a particular focus on the floods in Rio Grande do Sul (RS). The study aims to understand how the incorporation of these rights can influence social justice and quality of life, assessing the concrete effects of this approach in specific socio-environmental contexts. The research explores the evolution of the rights of nature within the legal framework, highlighting international experiences such as the 2008 Constitution of Ecuador, which recognizes nature as a subject of rights. Furthermore, it examines how these rights can promote the full restoration of ecosystems and ecological justice, addressing Alberto Acosta’s ideas on Buen Vivir as an alternative proposal to the traditional development model. Among the hypotheses investigated, it is considered that the recognition of the rights of nature may serve as an instrument to ensure sustainable development and enhance social justice in local communities, fostering a more equitable distribution of natural resources and strengthening community empowerment. On the other hand, the implementation of these rights may generate economic conflicts in areas dependent on natural resource exploitation, posing challenges to reconciling environmental protection with traditional economic practices. This dissertation is part of the research line Social Relations and Dimensions of Power, within the area of concentration New Paradigms of Law, in the Stricto Sensu Graduate Program – Master’s in Law at the School of Legal Sciences of the University of Passo Fundo. The study employs the deductive method and bibliographic research technique.